Fourier-Domain Low-Coherence Interferometry with Undetected Mid-Infrared Photons in the High-Gain Regime - Zotti, Giovanni; Hashimoto, Kazuki; Horoshko, Dmitri B.; Kolobov, Mikhail I.; Michael, Yoad; Gefen, Ziv; Chekhova, Maria V. (2025 Conference on Lasers and Electro-Optics, CLEO 2025, 2025)
We develop a high-parametric-gain SU(1,1) interferometer with an aperiodically-poled KTP crystal and demonstrate Fourier-domain low-coherence interferometry with undetected mid-infrared photons.
CRIS-Team Scopus Importer:2025-11-21